Learning Tendency Among Iraqi Children in Post-Conflict Communities - Tha'er Adnan Jameel (مجلة الباحث, 2025)
This study examines the factors influencing children's learning tendency (willingness) in post-conflict settings, with a specific focus on displaced students returning from Al-Hol and Al-Jad’a camps to their homes in Iraq. It also examines the impact of conflict on education and the learning environments of children. Drawing on a sample of 46 students aged 8–18, participants had lived in displacement for one to six years. They lacked access to formal and organized education. The research employs a mixed-methods approach using structured questionnaires. The data are analyzed quantitatively based on descriptive statistics like frequencies and percentages, while a qualitative approach is used in one open-ended question about respondents' future aspirations. The findings indicate that while trauma significantly reduced motivation to learn for most participants, factors such as family and teacher support, a sense of school safety, and informal educational programs played crucial roles in fostering resilience and learning willingness. Psychological benefits, including improved emotional well-being, were also reported. The study underscores the importance of integrating psycho-social support and trauma-informed teaching into post-conflict education systems and recommends stronger investment in informal learning environments as a bridge to formal schooling.